Recent Advances in Transition-Metal-Catalyzed Sonogashira Cross-Coupling Reactions of Alkyl Electrophiles - Zhao, Xian; Liu, Wei (Synthesis, 2023)
Catalytic Sonogashira cross-coupling reactions represent an efficient and versatile approach for constructing complex alkynes from readily available starting materials. Despite notable progress in this field, the development of transition-metal-catalyzed Sonogashira cross-coupling reactions of alkyl electrophiles remains limited. This limitation primarily stems from the low reactivity and pronounced propensity of these compounds towards β-H elimination. To overcome these challenges, researchers have investigated the use of palladium, nickel, and copper catalysts for Sonogashira reactions of alkyl electrophiles. Furthermore, significant strides have been made in achieving asymmetric Sonogashira cross-coupling reactions of electrophiles. This short review provides an overview of recent breakthroughs in this area.1 Introduction2 Palladium-Catalyzed Sonogashira Cross-Coupling of Alkyl Halides3 Nickel-Catalyzed Sonogashira Cross-Coupling of Alkyl Halides4 Copper-Catalyzed Sonogashira Cross-Coupling of Alkyl Electrophiles4.1 Copper-Catalyzed Racemic Sonogashira Cross-Coupling of Alkyl Electrophiles4.2 Copper-catalyzed Asymmetric Sonogashira Cross-Coupling of Alkyl Electrophiles5 Conclusions and Perspectives
Keywords: Sonogashira cross-coupling; alkyl electrophiles; palladium; nickel; copper; alkynes